Association between serum levels of vitamin D and chronic periodontitis in premenopausal women in Yazd - Razieh Eshghi; Fahimeh Rashidi Maybodi; Arezoo Khabazian; Shahab Shahhosseini (Babol University of Medical Sciences, 2016)
Introduction: Periodontal disease is a common chronic inflammatory disease, considered as a primary cause of tooth loss due to the destruction of periodontal tissues. Various studies have shown that vitamin D has anti-inflammatory and anti-microbial properties and plays a significant role in musculoskeletal health. There is strong evidence that vitamin D deficiency may increase the likelihood of osteoporosis and osteopenia as well as chronic inflammatory diseases such as periodontitis. Materials &Methods: This case–control study included 30 females with moderate or severe chronic periodontitis (CP) and 30 periodontally healthy females. The mean age of  the CP group   and the  control group was  34 years.  Indices of Probing depth (PD), clinical attachment level (CAL) and bleeding index (BI) as well as the serum level of vitamin D (1,25(OH)2D) were measured in both groups. The statistical analyses including t-tests, Pearson correlation coefficient and odd ratio. Results: There was a significant indirect relationship between the serum level of vitamin D and the periodontal indices (p<0.05). The odd ratio (OR) measures showed that subjects with vitamin D dose of less than 10 ng/ml were 5.6 times  more likely to have periodontitis compared to those with a normal dose of vitamin D ( p=0.03 ). Moreover, subjects with vitamin D dose of 10-29 ng/ml were about 1.46 times at a higher risk to develop periodontitis than those with sufficient dose of vitamin D (p>0.05). Conclusion: It is recommended that serum levels of vitamin D in patients with chronic periodontitis be measured and then if necessary, treatment should begin.